Application of the methods of monotonic sequences - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2023)
The method of monotonic sequences (see [1], [2]) is considered and the issue of its exactness is discussed. It is shown how the method can be applied to finite sums with a large number of summands.